Global Economy and Entrepreneurship - Kučinskienė, Marija; Jatuliavičienė, Gražina (Ekonomika, 2002)
Internationalization and globalization processes now transform the international economy into a global economy viewing the world, or relevant parts of the world, as a single market consisting of a number of segments defined by the products to be sold. To survive and prosper in it, companies will need to learn how to cope with the new business environment whether their companies are big or small, domestic or international. In the world entrepreneurship is linked at first with small and middle business enterprises. Also entrepreneurship is very actual for appearing of new and risky steps in Lithuania and for stimulation of economics. The experience of many foreign countries confirm significance of SME’s for economics growth. Unfortunately. entrepreneurship is not well known in all Lithuania. According to our research, in which directors of Lithuanian’s firms took place, a big part of them don’t know what entrepreneurship means and it is very bad. Because such a little country as Lithuania, in which there are no a lot resources, could be competitive only if we understand the significance of entrepreneurship. Due the increase of factor mobility the national state may create value added elsewhere, but not in the home country, especially using global innovation system as the basis for further entrepreneurship development.